Crack-channel polymer membrane based on sucrose fatty acid ester and preparation method thereof
By using sucrose fatty acid ester (SE) as additives in the membrane material, prepare a polymer film with a crack -like high pore structure, solve the problem of low surface opening rate and pollution of existing membrane materials, and achieve high permeability performance. And improve the resistance of anti -pollution.
Patent Information
- Application Number
- CN202211588036.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The surface porosity of existing membrane materials is low and the pore size distribution is wide, which makes it difficult to meet the ideal expectations of permeability and selection performance, and is easy to contaminate and affect the use effect.
Sucrose fatty acid ester (SE) was used as an additive to prepare a polymer membrane with a crack-like high-pore structure through a non-solvent phase inversion method to optimize the surface structure and anti-pollution performance of the membrane material.
It significantly improves the surface opening rate and overall porosity of the membrane material, improves the permeability and selectivity performance, and enhances the anti-pollution ability. The pure water flux can be as high as 1011.32±31.41L·m-2·h-1.
Smart Images

Figure CN116099380B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer film, in particular to a crack channel polymer film based on sucrose fatty acid ester (SE) and a preparation method thereof, and belongs to the technical field of film material preparation. Background Art
[0002] As a rapidly developing high-tech technology, membrane technology will play an important role in ensuring sustainable development, especially in the fields of sewage and wastewater treatment, water purification and water resource reuse. As an emerging water treatment technology, membrane technology not only has the functions of material separation, energy conversion, material transformation, controlled release, charge conduction, material identification, etc., but also has outstanding advantages such as high efficiency, energy saving, environmental protection, and easy operation. It has many advantages such as low investment, small footprint, and good effluent quality. It has become an economical and clean method for the current utilization of water resources. Therefore, membrane technology will escort the safety of the water environment and the utilization of sewage resources, and lay a technical foundation for the creation of a green industry.
[0003] The core of membrane technology lies in high-performance membrane materials, whose materials and micro-nano structures determine the separation characteristics and application scenarios of the materials. In the prior art, there are various methods for preparing membranes, among which non-solvent-induced phase inversion membrane preparation is the most commonly used method. The phase inversion process is a very complex thermodynamic and kinetic process, which includes many influencing factors, among which thermodynamic factors include polymer type and content, solvent type and content, non-solvent additive type and content, etc.; kinetic factors include gel bath type and temperature, post-treatment temperature and time, membrane thickness, etc. These factors can affect the path of the curing film formation process of the casting liquid system, thereby resulting in different membrane structures. This process has become the main preparation process for obtaining membrane materials because of its simplicity and easy scalability. The structure of the membrane material prepared by this process is usually an asymmetric morphology structure composed of a surface layer and a porous bottom layer that provides support. Its surface structure affects the main permeability and separation performance of the membrane. However, since the surface structure of the membrane obtained by this membrane preparation process is usually dominated by circular pores or irregular macropores, such as Figure 1 As shown, there are disadvantages of low membrane surface open porosity (generally less than 5%) and wide pore size distribution, which makes it difficult for the permeability and selectivity of the membrane material to reach ideal expectations.
[0004] In addition, during the use of the membrane, organic matter is easily adsorbed onto the surface or inner pore wall of the membrane, causing the membrane to easily form a filter cake layer during the filtration process, which in turn reduces separation efficiency and increases operating costs. Moreover, when microorganisms come into contact with the membrane, they will undergo reversible adsorption on the membrane surface through a variety of physical effects, and transform into an irreversible adsorption state with polysaccharides as anchors. The microorganisms then repeat the process of growth and reproduction, eventually forming a biofilm on the membrane surface, contaminating the entire membrane surface. Traditional membrane materials have low permeability due to membrane contamination, which affects the use effect.
[0005] In view of the above problems, how to optimize the surface structure of membrane materials, obtain high surface porosity while maintaining pore size uniformity and slow down the irreversible adsorption of pollutants on the membrane surface is a research difficulty and hot spot in the industry. Summary of the invention
[0006] The purpose of the present invention is to address the above-mentioned problems existing in the prior art, provide a crack-channel polymer membrane based on sucrose fatty acid ester and a preparation method, construct a high-porosity membrane material with a specific crack-like surface structure, achieve a dual-effect improvement in the membrane's fine selection ability and permeability performance, and optimize the anti-pollution performance of the membrane material.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention firstly discloses a crack-channel polymer membrane based on sucrose fatty acid ester (SE), and uses sucrose fatty acid ester (SE) as an additive to prepare a membrane material with a crack-like high-pore structure by a non-solvent-induced phase inversion method.
[0009] Preferably, the aforementioned membrane is a PMIA membrane, a PVDF membrane, a PES membrane, a PSf membrane or a PAN membrane, and the method is universal and applicable to many polymer membranes.
[0010] More preferably, the aforementioned polymer membrane is composed of a dense epidermal layer on the top and a finger-shaped porous bottom layer, and as the content of sucrose fatty acid ester increases, the non-porous region structure of the membrane gradually transforms into a porous loose structure; the formation of this porous structure helps to optimize the permeability of the membrane.
[0011] More preferably, the polymer membrane is PMIA, the mass percentage of sucrose fatty acid ester (SE) is 0.4wt.%, the surface opening rate of the obtained composite membrane can be as high as 15%, the overall porosity is 70%, and the pure water flux is higher than 1000L·m -2 ·h -1 The surface porosity of the composite membrane in the prior art is generally only 3-5%, and the optimal pure water flux is generally 700L·m -2 ·h -1 It can be seen that the surface open porosity and overall porosity of the composite membrane prepared in the present application are greatly improved, thereby significantly optimizing the permeability of the membrane material.
[0012] The present invention also discloses a method for preparing the aforementioned crack-channel polymer membrane based on sucrose fatty acid ester, comprising the following steps:
[0013] S1. Add SE to a polar solvent and stir to form a stable mixed solution;
[0014] S2. Add the polymer to the mixed solution, heat it to 70-100°C, fully dissolve it to form a uniform and stable casting solution, cool it down and let it stand for degassing, and form a membrane through a non-solvent induced phase separation method.
[0015] Preferably, the aforementioned polar solvent is DMF solvent, or a transparent homogeneous solution formed by mixing lithium chloride and DMAc.
[0016] Preferably, the aforementioned polymer is: PMIA, PVDF, PES, PSf or PAN. In the practical application of the method, it is not limited to the polymers listed above, and polymers that can form a film, such as PVC, PP, etc., can be expanded and applied.
[0017] More preferably, the mass percentage of the polymer is 10-20 wt.%, the mass percentage of the SE does not exceed 1 wt.%, and the rest is solvent.
[0018] More preferably, the addition amount of the aforementioned SE is 0.4wt.%, and the pure water flux of the composite membrane prepared by adding this amount increases to 1011.32±31.41L·m -2 ·h -1 The overall retention rate is maintained at around 80%, and the flux recovery rate is optimized to 50.38%. While effectively improving the permeability of the membrane, it can also give the membrane better pollution resistance and flux recoverability.
[0019] Further preferably, in the aforementioned step S2, the specific film forming method is: casting the film casting liquid on a glass plate, scraping it with a glass rod, and briefly staying in the air after the film scraping is completed, and then immersing the newly formed PMIA flat film in a deionized water coagulation bath at a temperature of 25°C. After phase separation and film formation, the prepared membrane is washed with deionized water, and finally stored in deionized water for standby use.
[0020] In addition, the raw materials in the preparation process of the present invention are non-toxic and the process is green and environmentally friendly. Therefore, the crack-channel polymer membrane based on sucrose fatty acid ester prepared by the present invention can be used not only in general industrial wastewater treatment, but also has excellent application prospects in the field of drinking water purification.
[0021] The present invention is beneficial in that:
[0022] (1) In the present invention, sucrose fatty acid ester (SE), a polyol-based nonionic additive, is used to prepare a polymer membrane. The microscopic effect of the amphiphilic properties of SE between the casting solution and the coagulation bath, as well as the microphase separation self-assembly strategy of SE itself, are utilized to regulate the multi-level scale membrane structure of the membrane material, so as to realize a high-porosity membrane material with a specific crack-like surface structure and achieve the uniformity of the surface pore size structure, thereby achieving a dual effect improvement in the fine selection ability and permeability of the membrane; it can also give the membrane material permanent hydrophilicity, further improving the membrane's anti-pollution ability.
[0023] (2) The surface structure of the polymer membrane prepared by the present invention is crack holes, which have a higher surface porosity and a better void structure than the traditional circular pore structure, thereby effectively improving the permeability of the membrane. The surface porosity of the membrane obtained by phase transformation in the prior art is only less than 5%, while the maximum surface porosity of the SE-modified membrane of the present application can reach about 10% or even up to 15%, which is 3 times higher than the membrane material prepared by traditional phase transformation. The overall porosity of the membrane can reach up to 71.51±0.72%, thereby obtaining a membrane material with high permeability, and the water flux can be as high as 1011.32±31.41L·m -2 ·h -1 , the interception rate remains at around 80%.
[0024] (3) The preparation method of the present invention has strong universality and is not only applicable to PMIA membranes, but also to different polymer membranes such as PVDF, PES, PSf and PAN. SE is a food-grade non-toxic additive. The preparation process is green, environmentally friendly and low-cost, which is of great practical significance for safely improving the quality of drinking water and improving the deteriorating water quality.
[0025] (4) The preparation method of the present invention can also overcome the bottleneck problem of deterioration of membrane mechanical properties caused by changing the casting liquid formula to increase membrane permeability in the existing process, and can better meet the market demand for new filter membrane materials with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The SEM image of the surface structure of the existing membrane material mentioned in the background technology;
[0027] Figure 2 The infrared spectra of SE raw materials, comparative examples and embodiments 1 to 4 are shown;
[0028] Figure 3 The SEM surface structure images of membranes M0 to M4;
[0029] Figure 4 The SEM surface structure images of membranes M5 to M8;
[0030] Figure 5 It is the SEM cross-sectional structure diagram of membranes M0 to M4;
[0031] Figure 6 The results of water contact angle measurement on the surface of membranes M0 to M4 are shown in the figure;
[0032] Figure 7 This is the image J software analysis chart of the surface porosity of membranes M0 to M4;
[0033] Figure 8This is the surface porosity analysis chart of membranes M5 to M8 using image J software;
[0034] Fig. 9 is the pore size distribution curve of membranes M0 to M4;
[0035] Fig.10 The pore size and porosity data of membranes M0 to M4 are shown in FIG.
[0036] Fig.11 It is a comparison chart of mechanical strength and elongation of membranes M0 to M4;
[0037] Fig.12 The figure is a comparison of the pure water flux and BSA retention performance of membranes M0 to M4;
[0038] Fig.13 The results of the three-cycle filtration experiment of the composite membrane using BSA as the simulated pollutant for membranes M0 to M4;
[0039] Fig.14 This is the flux recovery rate (FRR) result diagram of membranes M0~M4 in three-cycle filtration test. DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] Unless otherwise specified in the present invention, the raw materials used are commercially available, and the specific sources and specifications are as follows:
[0042] Name (abbreviation) Purity and molecular weight Manufacturer Polyacrylonitrile (PAN) 150000g / mol BASF Polyethersulfone (PES) 65000g / mol Solvay Corporation Polysulfone (PSf) 80000g / mol Solvay Corporation Polyvinylidene fluoride (PVDF) 800000g / mol Solvay Corporation Poly(m-phenylene isophthalamide) (PMIA) <![CDATA[M w ~140000g / mol]]> DuPont N,N-Dimethylacetamide (DMAc) 99.0% Shanghai MacLean Biochemical Technology Co., Ltd. Sucrose fatty acid esters (SE) <h2 style=";text-align:left;direction:ltr"><![CDATA[M <h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> <608.76g / mol<h2 style=";text-align:left;direction:ltr"> Hangzhou Ruilin Chemical Co., Ltd. Anhydrous lithium chloride (LiCl) 99.0% Shanghai MacLean Biochemical Technology Co., Ltd.
[0043] Table 1 List of raw materials / reagents used in the present invention
[0044] Comparative Example
[0045] At room temperature, 3.5wt.% lithium chloride and 82.5wt.% DMAc solvent were mixed and dissolved by high-speed stirring to form a transparent homogeneous solution. Then 14wt.% PMIA was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution, which was then cooled to 25°C and allowed to stand for degassing. After degassing, a membrane was formed by non-solvent induced phase separation method, named M0.
[0046] The specific film forming method is: casting the casting liquid on a glass plate, using a glass rod to scrape it, the thickness is controlled at 100 to 300 microns, after the film is scraped, it stays in the air with a humidity of 30 to 60% for 20 to 80 seconds, and then the newly formed PMIA flat membrane is immersed in a deionized water coagulation bath at a temperature of 20 to 30°C. After phase separation and film formation, the prepared membrane is washed with deionized water, and finally stored in deionized water for use.
[0047] Example 1
[0048] At room temperature, 3.5wt.% lithium chloride and 82.3wt.% DMAc solvent were mixed and dissolved by high-speed stirring to form a transparent homogeneous solution, and then 0.2wt.% SE was added to the solution and continued to stir until it dissolved into a uniform and stable solution. Then 14wt.% PMIA was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution, then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PMIA composite membrane was formed by a non-solvent induced phase separation method, named M1.
[0049] The specific film forming method is the same as above and will not be described in detail below.
[0050] Example 2
[0051] At room temperature, 3.5wt.% lithium chloride and 82.1wt.% DMAc solvent were mixed and dissolved by high-speed stirring to form a transparent homogeneous solution, and then 0.4wt.% SE was added to the solution and continued to stir until it dissolved into a uniform and stable solution. Then 14wt.% PMIA was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution, then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PMIA composite membrane was formed by a non-solvent induced phase separation method, named M2.
[0052] Example 3
[0053] At room temperature, 3.5wt.% lithium chloride and 81.9wt.% DMAc solvent were mixed and dissolved by high-speed stirring to form a transparent homogeneous solution, and then 0.6wt.% SE was added to the solution and continued to stir until it dissolved into a uniform and stable solution. Then 14wt.% PMIA was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution, then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PMIA composite membrane was formed by a non-solvent induced phase separation method, named M3.
[0054] Example 4
[0055] At room temperature, 3.5wt.% lithium chloride and 81.7wt.% DMAc solvent were mixed and dissolved by high-speed stirring to form a transparent homogeneous solution, and then 0.8wt.% SE was added to the solution and continued to stir until it dissolved into a uniform and stable solution. Then 14wt.% PMIA was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution, then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PMIA composite membrane was formed by a non-solvent induced phase separation method, named M4.
[0056] Example 5
[0057] At room temperature, 83.4wt.% DMF solvent and 0.6wt.% SE were stirred and dissolved into a uniform and stable solution, and then 16wt.% PAN was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution. The solution was then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PAN composite membrane was formed by a non-solvent induced phase separation method, which was named M5.
[0058] Example 6
[0059] At room temperature, 84.5wt.% DMF solvent and 0.5wt.% SE were stirred and dissolved into a uniform and stable solution, and then 15wt.% PVDF was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution. The solution was then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PVDF composite membrane was formed by a non-solvent induced phase separation method and was named M6.
[0060] Example 7
[0061] At room temperature, 81.6wt.% DMF solvent and 0.4wt.% SE were stirred and dissolved into a uniform and stable solution, and then 18wt.% PES was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution. The solution was then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PES composite membrane was formed by a non-solvent induced phase separation method and was named M7.
[0062] Example 8
[0063] At room temperature, 84.6wt.% DMF solvent and 0.4wt.% SE were stirred and dissolved into a uniform and stable solution, and then 15wt.% PSf was added to the solution and fully dissolved at 90°C to form a uniform and stable casting solution. The solution was then cooled to 25°C and allowed to stand for degassing. After degassing, a SE / PSf composite membrane was formed by a non-solvent induced phase separation method and was named M8.
[0064] Structural characterization and analysis
[0065] (1) Fourier transform infrared spectroscopy (FTIR)
[0066] Characterization method: After the prepared film sample is fully dried, it is fixed on the infrared test platform for infrared analysis. The spectrum is between 500 and 4000 cm -1 Scanning within the range with a resolution of 4cm -1 , the scanning times are 32 times, and the characterization results are as follows Figure 2 shown.
[0067] Depend on Figure 2 It can be seen that the membranes M0~M4 are at 3300cm -1There are broad absorption bands in the vicinity, which correspond to the stretching vibration of the NH bond in the PMIA structure; -1 The absorption vibration near the region corresponds to another characteristic peak of the PMIA structure, the stretching vibration of the CN bond; at 1480-1240cm -1 The peak in the region corresponds to the deformation vibration of the CH bond in PMIA, and the absorption intensity does not change with the increase of SE concentration. This shows that the prepared SE / PMIA composite membrane retains the chemical structure of the PMIA material itself, which is conducive to showing the good physical and chemical potential of PMIA polymer during membrane application, such as the good hydrophilicity and mechanical strength exhibited by CN and CH bonds.
[0068] It should be noted that from Figure 2 Visible, 3000~2800cm -1 The peaks are the stretching vibration absorption peaks of the CH group in SE. By comparing the CH absorption peak intensities of the SE films with different addition amounts, we found that: with the increase of SE addition in the film, the CH absorption peak intensity in the composite film increased significantly, which proves that SE has been compounded into the membrane material. Similarly, with the increase of SE addition, 1740cm -1 The stretching vibration peak of C=O also gradually appeared, which is the characteristic absorption peak of ester, further indicating that the preparation method of the present invention can successfully compound SE into the membrane material.
[0069] (2) Scanning electron microscopy (SEM)
[0070] Characterization method: The surface and cross-sectional morphology of the membrane were characterized by scanning electron microscopy (SEM, SUPRATM55, ZEISS, Germany). Before testing, the sample was sprayed with gold for 70 seconds to enhance the conductivity of the sample.
[0071] The surface and cross-sectional structure of the membrane were scanned by SEM to study the effect of additive SE on the membrane surface morphology. The results of comparative examples and examples 1 to 4 are shown in FIG. Figure 3 As shown, the results of Examples 5 to 8 are as follows Figure 4As shown. It can be seen that when no SE is added, the surface of the M0 membrane presents a typical phase transition circular pore and irregular pore structure morphology, which is similar to the background technology. With the addition of SE, the surface structure of the membrane gradually shows a trend of evolution of a crack-like structure morphology. When the SE content is 0.2wt% (M1), the M1 membrane is in a morphological feature of an irregular pore structure and a crack pore structure intertwined with each other. When SE is increased to 0.4wt% (M2), it can be seen that the membrane surface has completely presented a uniform crack-like pore structure feature. Similarly, the surfaces of membranes M5 to M8 also present a uniform crack-like pore structure. It can be seen that the additive SE can optimize the traditional circular pore structure on the surface of various polymer membranes into a crack-like pore structure, which plays a vital role in optimizing the performance of the composite membrane (pure water flux, retention rate and flux recovery rate, etc.), which will be described in detail later.
[0072] It can be seen that the addition of SE couples the phase inversion process and the self-assembly process of its surfactant, so that the surface porosity and regularity of the membrane are gradually improved. The applicant analyzed that on the one hand, it is attributed to the addition of SE that the exchange rate of phase inversion is increased, thereby gradually increasing the porosity of the membrane surface. On the other hand, as the SE content increases to 0.4wt.%, SE will be oriented on the membrane surface. Due to the microphase separation self-assembly, clusters with certain regular structures, such as rod-like structures, are formed, so that the membrane surface evolves into a crack-like structural morphology. When the SE content continues to increase to 0.6wt.% and 0.8wt.%, the crack-like pore structure of the membrane is reduced. This is mainly because with the increase of SE content, the viscosity of the polymer solution is increased, which changes the phase separation speed. At the same time, the increase in SE content improves the hydrophilic characteristics of the polymer solution system, thereby increasing the phase inversion rate. The structure of the membrane surface is transformed from SE self-assembly dominated to a phase inversion process dominated by rapid exchange of non-solvent and solvent, resulting in a gradual reduction in crack-like structures. It can be seen that Example 2 is a preferred embodiment.
[0073] Figure 5The cross-sectional morphology of membranes M0 to M4 is shown. It can be seen that all SE / PMIA membranes present a typical asymmetric structure at the microscopic level, consisting of a dense epidermis at the top and a finger-like porous bottom layer. Compared with M1, the finger-like pores of M2 become larger and the connectivity is enhanced as the SE concentration increases. However, when the SE concentration increases further, the finger-like macropores of the M4 membrane decrease instead. This may be due to the gradual increase in the content of PMIA polymer relative to the solvent when the SE content is high. That is, the further increase in the solid content in the casting solution leads to a slight decrease in the pores of the membrane sublayer. At the same time, it can also be found from the non-porous structure area of the membrane cross section that with the increase in SE content, the non-porous structure area also shows a development trend of increasing pore structure and enhancing loose characteristics. In summary, when no SE is added, the non-porous area of the M0 membrane cross section presents a dense structural morphology, but with the increase of SE, it can be clearly seen that the non-porous area structure of the membrane gradually changes to a porous loose structure.
[0074] In addition, it can be seen from the cross-sectional structure of the film that under the same scraping film operation process, as the amount of SE added increases, the thickness of the film increases slightly. The main reason may be that after the addition of additive SE, the viscosity of the casting liquid increases, and its castability weakens, resulting in an increase in film thickness. The film thickness data of each embodiment is shown in the following table:
[0075] Serial number Addition amount of SE (wt.%) Film thickness (μm) Comparative Example 0 131.5±2.5 Example 1 0.2 150.7±3.3 Example 2 0.4 157.3±2.3 Example 3 0.6 164.3±4.1 Example 4 0.8 169.5±6.7
[0076] Table 2 Film thickness of comparative examples and examples 1 to 4 with different SE addition amounts
[0077] (3) Characterization of the hydrophilicity and hydrophobicity of composite membranes
[0078] As we know, the hydrophilicity of the membrane surface is the key to its anti-fouling performance. Therefore, in the present invention, the hydrophilicity of the membrane is characterized by measuring the water contact angle on the membrane surface. The measurement results are as follows: Figure 6 The contact angle of the original PMIA film (M0) without SE added is 64.04±1.14°, which is already hydrophilic. The applicant analyzed that this is because the PMIA polymer contains hydrophilic amino groups and the PMIA molecular chains have hydrogen bonding forces, which provide a certain degree of hydrophilicity for the original PMIA film.
[0079] exist Figure 6It can be clearly observed that as the content of additive SE increases, the contact angle of the membrane surface gradually decreases from 64.04±1.14° to 49.47±4.31°, which indicates that the hydrophilicity of the membrane surface is enhanced. The applicant analyzed that this is mainly because: in order to reduce the Gibbs free energy at the two-phase interface and make the system tend to equilibrium, the additive SE can be oriented at the two-phase interface. To be precise, the hydrophilic groups in SE are oriented toward the polar phase (water) and the hydrophobic groups are oriented toward the non-polar phase (casting liquid). This directional arrangement of additives occurring at the two-phase interface during the phase separation process increases the roughness of the membrane surface. The hydrophilic hydroxyl segments in SE change the interaction force between the non-solvent and the solvent, forming a hydrophilic layer on the membrane surface, reducing the water contact angle and improving the hydrophilic properties of the membrane. At the same time, the hydrophobic ester group combines with the PMIA matrix through hydrophobic action, which helps to fix the SE molecules on the membrane surface to form permanent hydrophilic properties. Therefore, the introduction of additive SE can effectively improve the hydrophilic properties of the membrane surface, thereby optimizing the anti-fouling properties of the membrane.
[0080] (4) Composite membrane pore structure parameters
[0081] (a) Surface openness
[0082] From the above analysis, it can be seen that the additive SE has a crucial influence on the surface morphology (pore structure characteristics) of the composite membrane. Furthermore, the open porosity of the membrane surface was measured using the SEM surface structure image of the composite membrane and Image J software. Figure 7 The distribution diagram of the pore structure of the membrane surface after analysis and processing by image J software (membrane M0~M4) is given, in which the dark area represents the membrane pore structure. The software analyzes the data ratio of the total pore area to the total surface area of the membrane, and the surface porosity of the composite membrane is obtained. The specific measurement data results are shown in Table 3. Obviously, in the comparative example without adding SE (M0), its surface porosity is only 5.8690%. With the addition of SE additives, the surface porosity of M1-M4 membranes is significantly improved. The applicant analyzed that the main reason may be that the increase in the content of SE hydrophilic hydroxyl groups in the casting solution played an unexpected role in the film forming process, which promoted the two-phase interface to play the role of interface opening more efficiently. It should be noted that when the SE content increases from 0 to 0.4wt.%, the porosity of the membrane surface shows a trend of gradual increase, but when SE increases from 0.4wt.% to 0.8wt.%, the porosity of the membrane surface decreases instead.
[0083] In Example 2, when the SE content is 0.4wt.%, the porosity of the membrane surface is unexpectedly as high as 14.92%, which is the highest value of the surface porosity in each embodiment. In the SEM surface morphology analysis in the previous text, the M2 membrane has the most crack-like structures. It can be inferred from this that when the surface structure of the membrane evolves into a crack-like structure, the surface porosity of the membrane can be significantly improved. However, when the SE addition amount is greater than 0.4wt.%, the membrane surface porosity drops to about 12%, which may be due to the fact that when the relative content of SE in the casting solution is large, the content of PMIA polymer relative to the solvent increases, that is, in the unit test volume, the PMIA content increases and the solvent content decreases, resulting in a decrease in the membrane cavity. This may be because when the relative content of SE is large, the epidermal thickness of the top layer of the membrane also increases, but the cross-section of the composite membrane is mainly occupied by finger-like pores, which indicates that instantaneous phase separation is still the main film-forming mechanism of the casting solution. However, after adding the additive SE, especially when the relative percentage is high, the higher affinity between the hydrophilic segments and water greatly reduces the interaction between the PMIA matrix and the non-solvent (water). Therefore, compared with the casting solution without SE, the precipitation rate of the casting solution tends to slow down. That is, as the content of SE in the casting solution increases, there is a trend from instantaneous phase separation to delayed phase separation. The relative delayed phase separation produces a thicker epidermis, which slows down the solvent exchange and causes a slight decrease in the surface porosity of the membrane. However, compared with the surface porosity of the membrane without SE addition, SE has a significant effect on improving the surface porosity of the membrane.
[0084] In the same way, we analyzed the surface porosity of the membrane materials of other different polymers obtained in Examples 5 to 8. Figure 4 It can be seen that M5 to M8 are also polymer film materials with crack-like surface structures. Figure 8 The distribution diagram of the membrane pore structure of the four polymer membranes of Examples 5 to 8 when SE is used as an additive is given by using image J software, wherein the dark area represents the membrane pore structure. The surface porosity of the four polymer membranes is obtained by analyzing the data ratio of the total pore area to the total surface area of the membrane through software. The specific measurement data results are summarized in Table 3. It can be seen that the composite membrane obtained by the preparation method of the present invention has a higher surface porosity than that of the traditional phase separation membrane, and thus can significantly optimize the separation performance of the membrane, which will be described in detail later.
[0085] Serial number <![CDATA[Total surface area of the membrane (μm 2 )]]> <![CDATA[Total pore area on the membrane surface (μm 2 )]]> Surface opening rate (%) Comparative Example (M0) 2.277^1.54 0.206 5.8690 Example 1 (M1) 2.283^1.539 0.283 8.0560 Embodiment 2 (M2) 2.258^1.518 0.512 14.9200 Example 3 (M3) 2.275^1,52 0.3919 11.3320 Embodiment 4 (M4) 2.260^1.527 0.4487 12.9970 Example 5 (M5) 2.255^1.520 0.4022 11.7340 Example 6 (M6) 2.244^1.520 0.3924 11.5040 Example 7 (M7) 2.254^1.520 0.3076 8.9750 Embodiment 8 (M8) 2.275^1.524 0.3888 10.5730
[0086] Table 3 Summary of the results of the surface porosity of the membranes of the comparative examples and the examples
[0087] (b) Overall porosity
[0088] Characterization method: The pore size and pore size distribution of the membrane were measured using the membrane pore size analyzer Porolux1000.
[0089] Fig. 9 The pore size distribution curves of membranes M0 to M4 are shown. According to the trend of the distribution curves, the pore size distribution of the membranes is relatively narrow, indicating that the pore structure of the composite membrane prepared by the method of the present invention is relatively uniform and ideal.
[0090] Fig.10 The pore size and porosity data of the composite membrane are shown. As can be seen from the figure, with the increase of SE content, the average pore size of the membrane increases from 93.1±0.9nm to 109.1±1.07nm. The main reason is that the increase of SE hydrophilic hydroxyl content in the casting solution is conducive to the additive to play the role of interface opening more efficiently at the interface between the two phases, increasing the interaction force between the membrane surface and water molecules, promoting water diffusion into the membrane matrix, and making large pores appear on the surface of the cast membrane. It should be noted that when the SE content increases from 0 to 0.4wt.%, the porosity of the membrane shows a trend of gradual increase, but when SE increases from 0.4wt.% to 0.8wt.%, the porosity of the membrane gradually decreases.
[0091] In Example 2, when the SE content is 0.4wt.%, the membrane porosity reaches 71.51±0.72%, which is the highest porosity value of each example. Combined with the SEM surface structure in the previous text, it can be inferred that when the surface structure of the membrane evolves into a crack-like structure, the porosity of the membrane can be significantly improved. However, when the SE addition amount is greater than 0.4wt.%, the membrane porosity drops to about 61%, which may be due to the fact that when the relative content of SE in the casting solution is large, the content of PMIA polymer relative to the solvent increases, that is, in a unit test volume, the PMIA content increases and the solvent content decreases, resulting in a decrease in the membrane cavity. This may be because when the relative content of SE is large, the skin thickness of the top layer of the membrane also increases (see Figure 5 ), but the cross section of the composite membrane is mainly occupied by finger-like pores, which indicates that instantaneous phase separation is still the main membrane-forming mechanism of the casting solution. However, after the addition of the additive SE, especially when the relative percentage is high, the higher affinity between the hydrophilic chain segment and water greatly reduces the interaction between the PMIA matrix and the non-solvent (water). Therefore, compared with the casting solution without SE, the precipitation rate of the casting solution tends to slow down. That is: as the content of surfactant SE in the casting solution increases, there is a trend from instantaneous phase separation to delayed phase separation. The relative delayed phase separation produces a thicker epidermis, which slows down the solvent exchange and causes a slight decrease in the porosity of the membrane.
[0092] (5) Mechanical properties test of composite membrane
[0093] Testing method: The test was performed using an electronic general testing machine (AGS-J, Shimadzu Corporation, Japan). The dried film samples were cut into a size of 2 cm × 7 cm and tested using the device. The stretching speed of the device was set to 10 cm / min. Each sample was tested five times, and the average values of the tensile stress and stretch rate were taken.
[0094] The effects of adding different amounts of additives to the casting solution on the mechanical properties of PMIA membranes are shown in Figure 2. Fig.11 As shown, the mechanical properties of the membranes prepared in each embodiment are relatively close. Since the mechanical properties of polymer membranes are mainly affected by polymer concentration, porogen and type of coagulation bath, in the present application, the addition amount of SE is very small (no more than 1wt.%), the pore size and porosity of the composite membrane increase, resulting in an almost negligible decrease in the mechanical properties of the composite membrane.
[0095] Therefore, in the present invention, we surprisingly found that by adding a small amount of SE, the membrane permeability was greatly improved while the membrane mechanical properties were almost unaffected. In the application process of the membrane, the operating pressure was mostly maintained at 0.01-0.5MPa, and the composite membrane prepared in the present application obviously had sufficient mechanical strength. Therefore, the preparation method of the present application can break through the bottleneck problem of the deterioration of the membrane mechanical properties caused by changing the casting solution formula to increase the membrane permeability in the prior art.
[0096] Composite membrane filtration separation performance test
[0097] (1) Permeability
[0098] The permeability of the membrane was tested by a self-built cross-flow filtration test device. The schematic diagram of the device can be found in the previously applied patent 2022211662462. The membrane was cut into discs with a diameter of 7.8 cm and fixed in the membrane pool of the device. The test pressure was adjusted to 0.15 MPa and the flow rate was 2.5 L / min. The membrane was pre-pressed for 30 minutes until the water flux stabilized. Among them, the pure water flux J w1 (L·m -2 ·h -1 ) is calculated as follows:
[0099]
[0100] Where V is the volume of the permeate (L), S is the effective membrane area (m 2 ), t is the test time (h).
[0101] (2) Retention performance and flux recovery rate
[0102] The retention performance of the membrane was determined using BSA solution to simulate pollutants: 1 g / L BSA solution was placed in the feed tank of the cross-flow filtration device, and pre-pressed for 30 minutes until the permeate volume became stable, and the permeate volume was recorded. The permeate flux of the stabilized BSA solution was recorded as J. p The permeate and retentate of the BSA solution were collected, and the concentrations of the permeate and retentate at a wavelength of 278 nm were tested using a UV-visible spectrophotometer, and the retention rate was calculated using formula (2).
[0103]
[0104] Among them, C p is the permeate concentration; C f is the feed solution concentration.
[0105] Cleaning steps: After the BSA permeability test and the collection of the permeate, pure water is loaded into the feed tank in the cross-flow filtration device to physically clean the device (generally for 1 hour), during which the feed water is continuously replaced.
[0106] Measure the pure water flux again: put the pure water into the feed tank of the cross-flow filtration device and record the permeate volume under the operating pressure. The flux of the stabilized pure water obtained here is recorded as J w2 .
[0107] J p and J w2 The calculation method is the same as formula (1).
[0108] In this application, the flux recovery rate (FRR) is used to evaluate the fouling resistance of the membrane. FRR is the ratio of the calculated permeation flux after the polluted membrane is cleaned with pure water to the initial permeation flux. The higher the value, the better the membrane's anti-fouling performance, that is, the higher the proportion of reversible fouling. The calculation formula is shown in (3):
[0109]
[0110] In order to improve accuracy and reliability, a multi-cycle test stability was used. The first cycle was consistent with the above steps, and the FRR of the nth cycle was the ratio of the permeation flux at the end of the nth cycle to the initial permeation flux.
[0111] (3) Long-term stability test
[0112] Similar to the membrane permeability test process, the membrane was placed in a membrane pool of a cross-flow filtration device and subjected to a long-term stability test for 60 hours at a pressure of 0.1 MPa and a flow rate of 2.5 L / min.
[0113] The separation performance and permeability of the membrane are very important in production and use. The pure water flux and the retention capacity of 1g / L BSA of the membrane prepared in each embodiment were tested in this application. The results are as follows: Fig.12 As shown in the figure, as the SE content in the casting solution increases from 0 to 0.4wt.%, the pure water flux of the composite membrane increases from 632.33±16.75L·m -2 ·h -1 Increased to 1011.32±31.41 L·m -2 ·h -1 It can be seen that the change in the membrane pore structure optimizes the membrane permeability. By adding a certain amount of porogen SE, the membrane surface pore size and porosity show an increasing trend, allowing more water molecules to pass through the membrane, reducing the mass transfer resistance of water molecules in the membrane pores, and the surface structure of the membrane M2 of Example 2 evolves into a crack-like high-porosity regular structure, so that the membrane permeability reaches the maximum value. In addition, because the added SE contains hydrophilic hydroxyl segments, the hydrophilicity of the membrane surface is increased, the interaction between the membrane and the water molecules therein is increased, and the membrane permeability is further optimized.
[0114] When the SE addition amount was higher than 0.4wt.%, the pure water flux of the composite membrane decreased to 829.15±42.82L·m -2 ·h -1 , which is consistent with the test results of surface open porosity and overall porosity. It can be seen that although the surface pore size and hydrophilicity of the composite membrane increase due to the introduction of SE, when the relative content of the hydrophilic segment is larger, the chemical potential difference between the casting liquid and water decreases, and the phase conversion rate is relatively weakened, causing the cortex to thicken, thereby affecting the permeability of the membrane. This phenomenon shows that the permeability of the membrane can be significantly improved by adding an appropriate amount of porogen SE. At the same time, with the addition of SE, the retention rate of the BSA solution decreased from 88.28±1.08% to 69.71±1.54%, which is mainly attributed to the gradual increase in the pore size of the composite membrane. However, the overall retention rate of the prepared high-flux crack hole M2 membrane remains at around 80%.
[0115] Therefore, based on the comprehensive test results of water flux and BSA retention rate, it can be concluded that using SE as a porogen can effectively improve the filtration separation performance of the composite membrane.
[0116] We know that the pollutants in surface water are generally organic matter, which is easy to attach to the hydrophobic surface. Therefore, the hydrophilic surface of the modified membrane tends to resist the attachment caused by the adsorption of organic matter. In the present invention, 1g / LBSA solution was used as a pollutant to investigate the anti-fouling performance of the composite membrane. The results are as follows: Fig.13As shown. The BSA solution was put into the cross-flow filtration device as the feed liquid for testing. The results showed that the flux of all membranes dropped significantly, and the rapid loss of membrane permeability was attributed to membrane fouling. Specifically, BSA molecules were rapidly adsorbed and deposited on the membrane surface and in the membrane pores, causing the membrane pore size to shrink and thus reduce the permeability; at the same time, BSA molecules continued to deposit on the membrane surface to form a filter cake layer, which increased the membrane thickness. At the same time, the filter cake layer formed by the pollutants caused the BSA solute to continuously aggregate, causing concentration polarization, which greatly affected the permeability of the membrane.
[0117] The present invention conducted three cycle experiments and calculated the flux recovery rate (FRR) of the corresponding membrane to evaluate the specific anti-fouling performance of the membrane. Fig.14 As shown in the figure, the tertiary flux recovery rates of all composite membranes decrease continuously with the increase of cycle number. This is because in the simulated pollutant test, the irreversible pollution on the membrane surface will inevitably increase continuously.
[0118] The results show that the best permeability is the M2 composite membrane of Example 2, and the maximum flux recovery rate in the first cycle is 50.38±0.63%, which is attributed to the M2 membrane having a regular cracked membrane surface, the highest permeability and a moderately thick epidermis. It can be seen that by introducing SE to adjust the membrane surface structure to a cracked structure with a higher porosity while maintaining the uniform regularity of the cracked structure, the permeability of the membrane can be effectively improved, and the membrane can achieve better pollution resistance and flux recoverability.
[0119] In order to more clearly show the performance data of the membrane products of each embodiment, the following Table 4 summarizes the results of the above-mentioned characterization and performance tests of the comparative example and embodiments 1 to 4:
[0120]
[0121] Table 4 Summary of test results of comparative examples and membrane products of Examples 1 to 4
[0122] In summary, the present invention uses SE as an additive and adopts a non-solvent induced phase separation process to successfully design and prepare a new type of crack-channel polymer membrane, which is suitable for PMIA, PVDF, PES, PSf, and PAN. The chemical and physical structure, pore size, surface porosity, surface hydrophilicity, roughness, etc. of the composite membrane of the present invention are characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), pore size analyzer, Image J software and other characterization methods, and the comprehensive performance of the membrane material of the present invention, such as water flux, interception capacity, and anti-fouling properties, is verified. The results show that the additive SE has an important influence on the microstructure of the membrane. The present application utilizes the property of SE containing both hydrophilic and hydrophobic segments combined with the phase transformation membrane process to successfully design and prepare a membrane material with a crack-like high-porosity surface structure. In the optimal embodiment, the surface porosity of the composite membrane can be as high as about 15%, and the overall porosity can be as high as 70%, giving the membrane material particularly excellent permeability, and the pure water flux reaches 1000L·m -2 ·h -1 As mentioned above, the major discovery of this application is expected to provide new ideas for the film-forming formula design and preparation route of environmentally friendly polymer membranes, help to obtain filter membrane materials with excellent permeability, and show great development potential in the field of water treatment. Since the green and environmentally friendly food-grade additives used in the present invention are used, the membrane material has a good prospect in drinking water purification.
[0123] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a crack-channel polymer membrane based on sucrose fatty acid ester, characterized in that: The steps include: S1. Add SE to a polar solvent, wherein the amount of SE added is greater than or equal to 0.4 wt.% and less than 1 wt.%, and stir to form a stable mixed solution; the polar solvent is a transparent homogeneous solution formed by mixing lithium chloride and DMAc; S2. Add 10-20 wt.% of polymer PMIA into the mixed solution, heat to 70-100°C to fully dissolve, form a uniform and stable casting solution, cool and let stand to degas, and form a membrane by non-solvent induced phase separation. The specific film-forming method is: cast the casting solution on a glass plate, scrape it with a glass rod, and after scraping, let it stay in the air for a short time, and then immerse the newly formed PMIA flat membrane in a deionized water coagulation bath at a temperature of 25°C. After phase separation and membrane formation, wash the prepared membrane with deionized water, and finally store it in deionized water for use.
2. A crack-channel polymer membrane based on sucrose fatty acid ester, characterized in that: The preparation method according to claim 1 is adopted.
3. The crack channel polymer membrane based on sucrose fatty acid ester according to claim 2, characterized in that: The polymer membrane is composed of a dense epidermal layer on the top and a finger-shaped porous bottom layer. As the content of sucrose fatty acid ester increases, the non-porous region structure of the membrane gradually changes into a porous loose structure.
4. A crack-channel polymer membrane based on sucrose fatty acid ester according to claim 2, characterized in that: During the preparation, PMIA was used as the polymer and the mass percentage of sucrose fatty acid ester was 0.4 wt.%. The surface porosity of the obtained polymer membrane was as high as 15%, the overall porosity was 70%, and the pure water flux was higher than 1000 L·m -2 ·h -1 .
5. Application of the crack-channel polymer membrane based on sucrose fatty acid ester according to any one of claims 2 to 4 in the field of drinking water purification.
Citation Information
Patent Citations
Preparation method of support membrane for recovering hydrocarbon and support membrane prepared therefrom
KR1020100013617A
Porous polymer membrane for waste water treatment
WO2013022016A1
Cited By
Two-dimensional tetracarboxyl phenyl porphyrin copper nanosheet, photo-thermal pervaporation desalination membrane modified by same and application of photo-thermal pervaporation desalination membrane
CN120094405A
MOF thermal insulation layer enhanced photo-thermal composite desalination membrane and preparation method thereof
CN120885060A
A MOF-insulated layer-enhanced photothermal composite desalination membrane and its preparation method
CN120885060B